Stem Cells in Stroke Repair: Current Success & Future Prospects - Gopurappilly, Renjitha; Pal, Rajarshi; Krishna Mamidi, Murali; Dey, Sovan; Bhonde, Ramesh; Kumar Das, Anjan (CNS & Neurological Disorders - Drug Targets, 2011)
Stroke causes a devastating insult to the brain resulting in severe neurological deficits because of a massive loss of different neurons and glia. In the United States, stroke is the third leading cause of death. Stroke remains a significant clinical unmet condition, with only 3% of the ischemic patient population benefiting from current treatment modalities, such as the use of thrombolytic agents, which are often limited by a narrow therapeutic time window. However, regeneration of the brain after ischemic damage is still active days and even weeks after stroke occurs, which might provide a second window for treatment. Neurorestorative processes like neurogenesis, angiogenesis and synaptic plasticity lead to functional improvement after stroke. Stem cells derived from various tissues have the potential to perform all of the aforementioned processes, thus facilitating functional recovery. Indeed, transplantation of stem cells or their derivatives in animal models of cerebral ischemia can improve function by replacing the lost neurons and glial cells and by mediating remyelination, and modulation of inflammation as confirmed by various studies worldwide. While initially stem cells seemed to work by a ‘cell replacement’ mechanism, recent research suggests that cell therapy works mostly by providing trophic support to the injured tissue and brain, fostering both neurogenesis and angiogenesis. Moreover, ongoing human trials have encouraged hopes for this new method of restorative therapy after stroke. This review describes up-to-date progress in cell-based therapy for the treatment of stroke. Further, as we discuss here, significant hurdles remain to be addressed before these findings can be responsibly translated to novel therapies. In particular, we need a better understanding of the mechanisms of action of stem cells after transplantation, the therapeutic time window for cell transplantation, the optimal route of cell delivery to the ischemic brain, the most suitable cell types and sources and learn how to control stem cell proliferation, survival, migration, and differentiation in the pathological environment. An integrated approach of cell-based therapy with early-phase clinical trials and continued preclinical work with focus on mechanisms of action is needed.
Keywords: animal studies